Gut microbial characteristics in poor appetite and undernutrition: a cohort of older adults and microbiota transfer in germ‐free mice. Issue 4 (14th June 2022) - Fluitman, Kristina S.; Davids, Mark; Olofsson, Louise E.; Wijdeveld, Madelief; Tremaroli, Valentina; Keijser, Bart J.F.; Visser, Marjolein; Bäckhed, Fredrik; Nieuwdorp, Max; IJzerman, Richard G.
Abstract: Background: Older adults are particularly prone to the development of poor appetite and undernutrition. Possibly, this is partly due to the aged gut microbiota. We aimed to evaluate the gut microbiota in relation to both poor appetite and undernutrition in community‐dwelling older adults. Furthermore, we studied the causal effects of the microbiota on body weight and body composition by transferring faecal microbiota from cohort participants into germ‐free mice. Methods: First, we conducted a cross‐sectional cohort study of 358 well‐phenotyped Dutch community‐dwelling older adults from the Longitudinal Aging Study Amsterdam. Data collection included body measurements, a faecal and blood sample, as well as extensive questionnaires on appetite, dietary intake, and nutritional status. Appetite was assessed by the Council of Nutrition Appetite Questionnaire (CNAQ) and undernutrition was defined by either a low body mass index (BMI) (BMI < 20 kg/m 2 if <70 years or BMI < 22 kg/m 2 if ≥70 years) or >5% body weight loss averaged over the last 2 years. Gut microbiota composition was determined with 16S rRNA sequencing. Next, we transferred faecal microbiota from 12 cohort participants with and without low BMI or recent weight loss into a total of 41 germ‐free mice to study the potential causal effects of the gut microbiota on host BMI and body composition. Results: The mean age (range) of our cohort was 73 (65–93); 58.4% was male. Seventy‐seven participants were undernourished and 21 participants had poor appetite (CNAQ < 28). A lower abundance of the genus Blautia was associated with undernutrition (log2 fold change = −0.57, Benjamini–Hochberg‐adjusted P = 0.008), whereas higher abundances of taxa from Lachnospiraceae, Ruminococcaceae UCG‐002, Parabacteroides merdae, and Dorea formicigenerans were associated with poor appetite. Furthermore, participants with poor appetite or undernutrition had reduced levels of faecal acetate ( P = 0.006 and 0.026, respectively). Finally, there was a trend for the mice that received faecal microbiota from older adults with low BMI to weigh 1.26 g less after 3 weeks ( P = 0.086) and have 6.13% more lean mass (in % body weight, P = 0.067) than the mice that received faecal microbiota from older adults without low BMI or recent weight loss. Conclusions: This study demonstrates several associations of the gut microbiota with both poor appetite and undernutrition in older adults. Moreover, it is the first to explore a causal relation between the aged gut microbiota and body weight and body composition in the host. Possibly, microbiota‐manipulating strategies will benefit older adults prone to undernutrition.